2023
DOI: 10.1002/ep.14210
|View full text |Cite
|
Sign up to set email alerts
|

A study on the microbial biocorrosion behavior of API 5 L X65 carbon steel exposed to seawater

Abstract: Despite much progress achieved, corrosion in oil and gas pipelines remains a concern due to industrial failures, and environmental and economic damages. Oil and gas pipeline failures are very common as a result of the natural degradation of carbon steel exposed to the marine environment. It has been reported that the presence of microorganisms in seawater contributes to the intensification of corrosion and subsequent biofilm formation on metal surfaces. Few scientific publications have investigated the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This increase in the corrosion rate was due to the production of a corrosive byproduct, H 2 S, by SRB. This byproduct reacts with carbon steel to form FeS, which is corrosive [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in the corrosion rate was due to the production of a corrosive byproduct, H 2 S, by SRB. This byproduct reacts with carbon steel to form FeS, which is corrosive [43].…”
Section: Discussionmentioning
confidence: 99%
“…The pitting and sulphur deposit on the surface of carbon steel, indicating the production of hydrogen sulphide as a byproduct of its metabolism reacting with the metal surface to form FeS [43]. It was observed that more sulphur deposits were detected via EDX in the PMB media, resulting in severe pitting on the carbon steel surface.…”
Section: Discussionmentioning
confidence: 99%